Are the Weak Measurements Really Measurements? - Dmitri Sokolovski (Quanta)
Weak measurements can be seen as an attempt at answering the Which way? question without destroying interference between the pathways involved. Unusual mean values obtained in such measurements represent the response of a quantum system to this forbidden question, in which the true composition of virtual pathways is hidden from the observer. Such values indicate a failure of a measurement where the uncertainty principle says it must fail, rather than provide an additional insight into physical reality.